Studi Komparasi Penggunaan Model Pembelajaran Discovery Learning Dan Project Based Learning dalam Meningkatkan Partisipasi Belajar Pada Mata Pelajaran Prakarya dan Kewirausahaan Siswa Kelas XI SMKN 9 Surakarta Tahun Ajaran 2015/2016 - Nihayah, Naulil Maghfirotun; , Drs. Joko Suwandi, SE. M.Pd (2016)
Student participation is very important in learning activities in the classroom. This research aims to determine the differences in students participation with learning methods Discovery Learning and Project Based Learning. This type of research is an experimental research and data collection techniques using observational methods and test methods. The results showed that the use of learning methods Discovery Learning and Project Based Learning in increasing students participation at SMK 9 Surakarta namely Comparison to the control class (Discovery Learning) with an average value of 82.84, while the experimental class (Project Based Learning) to the average value -rata at 73.32. It can be concluded that "There is a difference in the use of learning model Discovery Learning Multimedia XI B (control group) and Project Based Learning XI Computer Network (class of experiments in increasing the participation of students in the subjects of craft and Entrepreneurship class XI student at SMK 9 Surakarta.